2022
DOI: 10.1021/acssuschemeng.2c04056
|View full text |Cite
|
Sign up to set email alerts
|

Dual-Templating Approach for Engineering Strong, Biodegradable Lignin-Based Foams

Abstract: Technical lignins are generated as byproducts from the wood pulping industry. Although their estimated annual production amounts to approximately 70 million tons, their exploitation as valueadded products remains insignificant. Yet, the diversity in the molecular structure and surface chemistry of technical lignins and their intrinsic role as mechanical support of plants may be an asset to consider in the engineering of plant-inspired materials such as biofoams. Valorization of lignins into solid foams, howeve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(20 citation statements)
references
References 58 publications
0
20
0
Order By: Relevance
“…to organize the self-assembly of biological tissue. Another example is provided in a report by Trovagunta et al (2022), wherein the cellulose nanofibrils (CNFs) were used as a template to align lignin particles using an oriented freezing front method. Fig.…”
Section: CLmentioning
confidence: 99%
See 3 more Smart Citations
“…to organize the self-assembly of biological tissue. Another example is provided in a report by Trovagunta et al (2022), wherein the cellulose nanofibrils (CNFs) were used as a template to align lignin particles using an oriented freezing front method. Fig.…”
Section: CLmentioning
confidence: 99%
“…to prepare scaffold structures from different forms of cellulosic nanomaterials, together with chitosan. Trovagunta et al (2022) reported the formation of lignin-based foams, having a high degree of directionality, by use of an oriented freezing front method.…”
Section: Ice Icementioning
confidence: 99%
See 2 more Smart Citations
“…PUrFs show typical three-stage compression profiles for cellular solids. 39 A first linear elastic region can be defined at low strain (up to 10%), in which deformation primarily occurs due to the elastic bending of cell walls. The second phase corresponding to a plateau region (from 10% to 50% strain) attributes to the collapse of cell walls.…”
Section: Influence Of Nano Sio 2 Content On Properties Of Purfsmentioning
confidence: 99%